The development of doping use in high-level cycling: From team-organized doping to advances in the fight against doping - Lentillon-Kaestner, V. (Scandinavian Journal of Medicine & Science in Sports, 2013)
In 1998, the Festina scandal at the Tour de France provided the first proof of widespread doping in professional cycling. This doping scandal marked the end of team-organized doping in professional cycling and ushered in a new period marked by the increasing implementation of anti-doping measures. This article evaluates the impact of the anti-doping rules and tests instituted since the Festina scandal. We adopt a psychosocial approach to analyze the organization of doping and the development of doping attitudes and practices in high-level cycling. Sixteen cyclists were interviewed, of which eight were young, current cyclists and eight were former cyclists who became professionals before the Festina scandal. Our results show that although the fight against doping in the last decade has reduced doping use in high-level cycling, anti-doping measures have also had unexpected effects. The fight against doping in cycling is not over.